Great people decisions why they matter so much, why they are so hard, and how you can master them - Fernandez Araoz, Claudio (Hoboken John Wiley & Sons, 2007)
Great organizations are made up of great people. And for leaders at all levels within those organizations, the ability to find, hire, integrate, and retain great people is an absolutely critical skill?critical to their organization's success, and critical to their own success.
Includes bibliographical references (p. 297-300).
Keywords: Executives--Recruiting.